Genome-wide analysis of Udai21: Unraveling the genetic basis of superior eating quality in rice - Hiroki Ikeda; Masatsugu Tamura; Takayuki Ohnishi; Kenta Shirasawa (PLoS ONE, 2025)
Rice ( Oryza sativa L.) is a staple for more than half of the world’s population, and grain quality strongly influences consumer preference and market value. Udai21, also referred to as Ohkome21, and previously designated as Yudai21, is a Japanese japonica cultivar noted for excellent eating quality and storage performance, yet its breeding origin and genomic basis remain unclear. Here, we aimed to resolve the genomic composition and likely parental origins of Udai21, and to identify candidate genes related to its distinctive quality traits. We generated a chromosome-scale assembly using PacBio HiFi long reads and assessed within-cultivar uniformity by sampling two breeder-maintained lines. We then profiled population structure using double digest restriction-site associated DNA sequencing together with representative accessions and conducted whole-genome resequencing and organelle genome analysis to trace ancestry, map polymorphisms, and annotate predicted impacts. Udai21 was predominantly japonica but carried introgressed aus-derived segments on chromosomes 1, 2, 3, 6, 7, and 10. Organelle single-nucleotide polymorphisms placed Udai21 with the aus cluster, consistent with an aus maternal origin and a japonica (Koshihikari) paternal contribution. The two maintenance lines showed high genetic uniformity. Among 37,522 predicted genes, we identified 1,017 non-redundant genes harboring high- or moderate-impact variants relative to Koshihikari, including loci previously implicated in grain quality and starch metabolism. These results support a hybrid origin for Udai21 (aus × Koshihikari) and provide a curated genome resource and candidate loci that can enable marker-assisted selection and informed crossing to combine superior eating quality with postharvest stability.